Adult hypertrophic pyloric stenosis due to peptic ulcer disease: a rare presentation - Deen, Shameer; Bakshi, Vipin Kumar; Singh, Siddharth Jai; Bohara, Satish K.; Dutt, S. C. (International Journal of Research in Medical Sciences, 2016)
Primary adult hypertrophic stenosis is uncommon with an uncertain etiopathogenesis and associated gastric outlet obstruction mimics gastric carcinoma. We present a case of AHPS as sequel of peptic ulcer disease in a 72 year old male. With the advent of proton pump inhibitors as a mainstay of medical therapy, complication into gastric outlet obstruction is a rare disease today. Upper GI endoscopy revealed a distended stomach, residual food and a hyperemic bulky pylorus not accommodating the endoscope. Barium meal follow-through revealed a dilated stomach and minimal barium passing through the pylorus. Histological analysis revealed mild dysplasia at the focus with dense inflammatory infiltrates composed of lymphocytes and eosinophils in the lamina propria. No evidence of malignancy was noted, favouring chronic gastritis. The condition mimics other forms of proliferative disorders like carcinoma, gastrointestinal stromal tumors. We present the clinical findings, imaging analysis and discuss etiopathogenesis and management.